The Relationship Between Donations and Individual Happiness: An Analysis of Prosocial Spending Effects Among Muslims in Indonesia - Khoiriyah, Nur Faizah; Paksi, Girindra Mega (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
Indonesia is renowned for its cultural diversity, with the tradition of gotong royong—symbolizing solidarity and mutual assistance—deeply embedded in its society. This tradition is mirrored in the country's high level of philanthropic activity, making Indonesia the most generous nation globally. This study investigates the relationship between charitable donations and the happiness of Indonesia’s Muslim population, using data from the 2014 Indonesian Family Life Survey (IFLS) wave 5, which represents about 83% of individuals living in 13 out of 33 provinces. The focus on the Muslim population reflects their substantial contribution to Indonesia’s global ranking in generosity. Four control variables—health, education, consumption (food and non-food), and social participation—are included in the analysis, which is conducted using binary logistic regression. The findings indicate that donations have a significant positive impact on the happiness of Muslims in Indonesia. Moreover, three control variables—health, education, and food consumption—also show positive and significant effects, while social participation, despite its theoretical relevance, does not exhibit a significant impact. Although non-food consumption is statistically significant, it presents an odds ratio of 1, suggesting no meaningful influence on happiness.